Thermal Prestressing of Structural Steel - Wichman, Sven H. (Engineering Journal, 1965)
The thermal prestressing method discussed in this article consists of shop welding heated high strength steel cover plates to the bottom flanges of beams and girders. Heat is produced with a simple device, such as a gas torch; elongation of the plate is measured with a dial indicator. After cooling, the plate creates predetermined favorable stresses in the beam which in effect permit less steel to do more work. Considering all costs, the savings over conventional construction are shown to amount to about 6 percent. Advantages, limitations and proposed applications of the method are discussed. Underlying theory is limited to end results.